Preformed T cell alloimmunity and HLA eplet mismatch to guide immunosuppression minimization with tacrolimus monotherapy in kidney transplantation: Results of the CELLIMIN trial. Issue 8 (15th April 2021) - Bestard, Oriol; Meneghini, Maria; Crespo, Elena; Bemelman, Frederike; Koch, Martina; Volk, Hans D.; Viklicky, Ondrej; Giral, Magali; Banas, Bernhard; Ruiz, Juan C.; Melilli, Edoardo; Hu, Liu; et al.
Abstract : Personalizing immunosuppression is a major objective in transplantation. Transplant recipients are heterogeneous regarding their immunological memory and primary alloimmune susceptibility. This biomarker‐guided trial investigated whether in low immunological‐risk kidney transplants without pretransplant DSA and donor‐specific T cells assessed by a standardized IFN‐γ ELISPOT, low immunosuppression (LI) with tacrolimus monotherapy would be non‐inferior regarding 6‐month BPAR than tacrolimus‐based standard of care (SOC). Due to low recruitment rates, the trial was terminated when 167 patients were enrolled. ELISPOT negatives (E−) were randomized to LI ( n = 48) or SOC ( n = 53), E+ received the same SOC. Six‐ and 12‐month BPAR rates were higher among LI than SOC/E− (4/35 [13%] vs. 1/43 [2%], p = .15 and 12/48 [25%] vs. 6/53 [11.3%], p = .073, respectively). E+ patients showed similarly high BPAR rates than LI at 6 and 12 months (12/55 [22%] and 13/66 [20%], respectively). These differences were stronger in per ‐ protocol analyses. Post‐hoc analysis revealed that poor class‐II eplet matching, especially DQ, discriminated E− patients, notably E−/LI, developing BPAR (4/28 [14%] low risk vs. 8/20 [40%] high risk, p = .043). Eplet mismatch also predicted anti‐class‐I ( p = .05) and anti‐DQ ( p < .001) de novo DSA. Adverse events were similar, but E−/LI developed fewer viral infections, particularly polyoma‐virus‐associated nephropathy ( p = .021). Preformed T cell alloreactivity and HLA eplet mismatch assessment may refine current baseline immune‐risk stratification and guide immunosuppression decision‐making in kidney transplantation. Abstract : In a multicenter, randomized, biomarker‐guided trial assessing pretransplant donor‐reactive memory T cells for immunosuppression minimization in kidney transplant recipients, both absence of preformed cellular alloreactivity and optimal HLA class II molecular matching identified patients who could be maintained on tacrolimus monotherapy at 1 year after transplantation.